Examining The Relationship Between Police Brutality and State- Sanctioned Violence: Impacts on Civil Liberties and Public Trust in Law Enforcement - Ranawaka, R.A.H.D.N. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
Police brutality, defined as the excessive or unlawful use of force by law enforcement officers, is closely linked to broader forms of state-sanctioned violence. Legal frameworks such as Emergency Regulations have, in certain contexts, legitimised coercive policing practices which, when combined with police brutality, contribute to the restriction of civil liberties, particularly the rights to freedom from torture, personal liberty, and freedom of expression. These practices have also significantly eroded public trust in law enforcement institutions. This study focuses on Sri Lanka due to its recent history of police brutality and state-sanctioned violence, particularly in the application of laws such as the Prevention of Terrorism Act. Through selected case studies involving judicial decisions, documented incidents of police brutality, and institutional responses, the research examines how these practices are interrelated and how they contribute to the erosion of fundamental rights. The study further analyses the impact of such practices on democratic governance, including reduced public cooperation with the police, declining crime reporting, and increased social unrest. The research adopts a qualitative doctrinal and sociolegal methodology. This includes legal analysis of relevant statutes and case law, complemented by thematic analysis of documented incidents of police brutality. Secondary public opinion data is utilised, drawing on reports published by human rights organisations, commissions of inquiry, and prior empirical studies assessing public perceptions of law enforcement. The findings demonstrate that repeated instances of police brutality, often justified on grounds of public order and national security, disproportionately affect marginalised communities and undermine public confidence in law enforcement agencies. The study concludes that sustained state tolerance of excessive police force weakens democratic governance and highlights the urgent need for reform of Sri Lanka’s legal and institutional policing frameworks through stronger oversight, enhanced accountability, and a shift towards rights-based policing.
Keywords: Police brutality; Public trust; Human rights; Freedom from torture